Quantum mechanics - Schwabl, Franz (Berlin: Springer Verlag, 2007)
This introductory course on quantum mechanics is the basic lecture that precedes and completes the author's second book Advanced Quantum Mechanics. This new edition is up-to-date and has been revised. Coverage meets the needs of students by giving all mathematical steps and worked examples with applications throughout the text as well as many problems at the end of each chapter. It contains nonrelativistic quantum mechanics and a short treatment of the quantization of the radiation field. Besides the essentials, the book also discusses topics such as the theory of measurement, the Bell inequality, and supersymmetric quantum mechanics.
Appendix 399-415p.; Index 417-423p.
Keywords: Quantum mechanics; Physics